Ответы и объяснения

2013-04-26T08:41:13+00:00

1)-2,4x=3,16-10 
-2,4x=-6,84 
x=-6,84/(-2,4) 
x=2,85

2)

2.3y+60.03=70.84

2.3y=70.84-60.03

2.3y=10.81

y=10.81:2,3

y=4.7

3)
(z - 1,2)/0,6 = 21,1
z - 1,2 = 21,1 * 0,6
z - 1,2 = 12,66
z = 12,66 + 1,2
z = 13,86
4)
3,5m + m = 9,9
4,5m = 9,9
m = 2,2

2013-04-26T08:42:06+00:00

10-2,4x=3,16

-2,4х=3,16-10

-2,4х=-6,84

х=2,85

 

 (y+26,1)*23=70,84

23y+600,30=70,84

23y=70,84-600,30

23y=-529,46

y=-23,02

 

(z-1,2)/0,6=21,1

z-1,2=21,1*0,6

z-1,2=12,66

z=12,66-1,2

z=11,46

 

3б5m+m=9,9

366m=9,9

m=0,03